Examining the Knowledge and Capacity of Elementary Teachers to Implement Classroom Physical Activity Breaks - Danae M. DINKEL; Jung-Min LEE; Connie SCHAFFER (International Electronic Journal of Elementary Education, 2016)
This study examined teachers’ zone of proximal development for classroom physical activity breaks by assessing teachers’ knowledge and capacity for implementing classroom physical activity breaks. Five school districts of various sizes (n=346 teachers) took part in a short online survey. Descriptive statistics were calculated and chi-square analyses were used to identify differences between districts. Almost all teachers utilized classroom physical activity to some extent. A third of teachers who stated they implemented classroom physical activity, experienced barriers to implementation. A majority of teachers were interested in learning more about classroom physical activity. There were significant differences between districts on the number of days per week classroom physical activity was integrated, the frequency of collaboration that occurred between teachers, the percentage of teachers who experienced barriers, and preferred delivery method of professional development. These findings support the importance of identifying teachers’ zone of proximal development to increase the use of classroom physical activity breaks. Understanding teachers’ knowledge and capacity for implementing classroom physical activity breaks can allow educational professionals to shift the implementation of classroom physical activity beyond sporadic use by isolated teachers and schools to a more systematic and consistent delivery across classrooms and throughout districts.